Penerapan Scientific Learning Untuk Meningkatkan Hasil Belajar Siswa Kelas 2 SD Bab “Keluargaku Unik” - Indiana Zulfia Malik; Puji Rahayu; Tri Eko Baktiono (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aimed to improve the learning outcomes of second-grade students at SD Negeri Latsari Tuban in Indonesian language lessons, specifically focusing on the theme